Facilitation of bronchoscopy teaching with easily accessible low-cost 3D-printing. (August 2017) - Osswald, Martin; Wegmann, Annigna; Greif, Robert; Theiler, Lorenz; Pedersen, Tina H.
Abstract: Background: Bronchoscopy is a challenging skill and anaesthesia and pulmonologist societies recommend simulation for practicing. Aim: The goal of this project was to develop a bronchoscopy simulator that allows critical-event simulation at low costs. Methods: Following written informed consent, we processed a human computer-tomography scan and extracted information about the bronchial tree. We then printed two bronchial trees in a 3D-printer in two different materials: hard polyamide and flexible photopolymer. The simulators were coated with silicone for a realistic appearance. Two independent airway expert consultant anaesthesiologists assessed the face validity of the simulators when compared to humans and to a commercially available bronchial tree simulator. Results: The two airway experts agreed on face validity and the 3D-simulators were deemed as highly comparable to the human anatomy, representing the human trachea and bronchial tree more realistically than the commercially available simulator. However, the flexible 3D-printed simulator was not satisfactory because the flexible texture allowed for easy damage of the silicone coat. Conclusion: We have described a simple method to create a low-cost bronchoscopy simulator with high anatomic fidelity using 3D-printing. The simulator features the ability to simulate advanced bronchoscopy tasks. Highlights: From CT-scans to 3D-printable images with only open-source graphic software programs. 3D-printed, cost-effective, realistic bronchial tree simulator for bronchoscopy training. Two airway experts deemed the simulator as highly comparable to human anatomy. Features the ability to simulate advanced bronchoscopy tasks.